1968
DOI: 10.1042/bj1090825
|View full text |Cite
|
Sign up to set email alerts
|

The binding of sodium dodecyl sulphate to various proteins

Abstract: 1. The binding of sodium dodecyl sulphate to proteins by equilibrium dialysis was investigated. 2. Most of the proteins studied bound 90-100% of their weight of sodium dodecyl sulphate. 3. The glycoproteins studied bound 70-100% of their weight of sodium dodecyl sulphate, calculated in terms of the polypeptide moiety of the molecule. 4. Proteins not containing S.S groups bound about 140% of their weight of sodium dodecyl sulphate. 5. Reduction of four proteins containing S.S groups caused a rise in sodium dode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
149
2
5

Year Published

1972
1972
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 493 publications
(168 citation statements)
references
References 13 publications
12
149
2
5
Order By: Relevance
“…Moreover, if the degree of SDS adsorption by glycans found here (0.2 g/g) is general, the difference between peptides and glycans might be more pronounced for other glycoproteins. This suggestion is in accord with the study by Pitt-Rivers and Impiombato [21], who found that saturation occurred at around 1.0 g/g peptide for a range of different proteins whether glycosylated or not. While the contribution from the glycans cannot be unambiguously discerned from the variability among the different proteins studied by these workers, this result indeed suggests very low SDS binding to glycans.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, if the degree of SDS adsorption by glycans found here (0.2 g/g) is general, the difference between peptides and glycans might be more pronounced for other glycoproteins. This suggestion is in accord with the study by Pitt-Rivers and Impiombato [21], who found that saturation occurred at around 1.0 g/g peptide for a range of different proteins whether glycosylated or not. While the contribution from the glycans cannot be unambiguously discerned from the variability among the different proteins studied by these workers, this result indeed suggests very low SDS binding to glycans.…”
Section: Discussionsupporting
confidence: 92%
“…To address the effects of glycosylation on the SDS-induced destabilization, and to determine the relative affinity of the detergent for the peptide and glycan moieties, we compared data for Phy with results for an enzymatically deglycosylated form (dgPhy). The importance of glycoprotein-surfactant interrelationships has been pointed out already in the seminal work of Pitt-Rivers and Impiomba [21], but none of the nearly 500 papers quoting this publication has addressed the problem. Recently, progress has been made in the understanding of surfactant interactions with soluble oligosaccharides [28][29][30][31], but protein conjugated glycans remain practically unexplored.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This is appreciably higher than the value of 0.9g/g found for the non-reduced protein by Pitt-Rivers & Impiombato (1968), presumably as a result of the higher concentration of sodium dodecyl sulphate used in the present work. The denaturation profiles, i.e.…”
Section: Resultscontrasting
confidence: 75%
“…Unreacted samples or crosslinked material were expected to migrate at different positions since it has been reported that, after reaction with dimethyl suberimidate, migration of proteins is slightly slowed down, probably because the binding of sodium dodecylsulfate is reduced after amidation [7]. Therefore two calibration curves have been established.…”
Section: Crorrlinking Bet Ween Subunits and Moleculur Weight De Fenmentioning
confidence: 99%